Birefringence Control in Silicon Wire Waveguide by Using Over-etch - Ika Puspita; Agus Muhamad Hatta (IAES Indonesian Section, 2017)
Silicon wire waveguide technology becomes great issue in optical communication system. The high index contrast of the silicon wire waveguide induced the birefringence. It played important role in silicon wire waveguide loss since it caused polarization dependent loss (PDL), polarization mode dispersion (PMD) and wavelength shifting. Hence, suitable controlling birefringence in silicon wire waveguide becomes very important. The current birefringence controlling techniques by using cladding stress and geometrical variation in bulk silicon waveguide was presented. Unfortunately, it could not obtain zero birefringence when applied to silicon wire waveguide. The over-etching technique was employed in this paper to obtain zero birefringence. The tall silicon wire waveguide obtained minimum birefringence.